Figures and Leadership Commitment in Implementing the Functions of Farmer Groups in Bumi Ayu Village, Dumai City - shaliza, fara; Yulia; Rahayu, Sri; Roza, Jumita (Balai Pelatihan Pertanian Jambi, 2023)
Farmer groups have a function as a learning class, a vehicle for cooperation, and a production unit. Through leadership figures and commitment, it is hoped that farmer groups can carry out their functions. The aims of this study were (1) to analyze the leadership figure of farmer group leaders in carrying out farmer group functions, and (2) to analyze the leadership commitment of farmer group leaders in implementing farmer group functions. The method used is a qualitative research method with a case study approach. The data used are primary and secondary data obtained from observations, in-depth interviews, documentation, and reports. The data analysis technique used Miles and Huberman's interactive analysis, while the data validity technique used data source triangulation and data collection techniques. The results showed that the head of the Sri Gemilang Farmers Group was a transformational leadership figure. The function of farmer groups is carried out through the use of information and communication technology, good administration, upgrading farmer group classes, development of food crop commodities, growing millennial farmers, utilization of peatlands for horticulture cultivation, and alsintan assembly services. The Head of the Sri Gemilang Farmers Group implements ten commitments in carrying out the functions of farmer groups.